Resurgence of Schmallenberg Virus in Belgium after 3 Years of Epidemiological Silence. Issue 5 (2nd August 2016) - Delooz, L.; Saegerman, C.; Quinet, C.; Petitjean, T.; De Regge, N.; Cay, B.
Summary: In spring 2016, three years after the last reported outbreak of Schmallenberg virus (SBV) in Belgium, an abortion was notified in a two year old Holstein heifer that previously had not been vaccinated against SBV. The autopsy of the eight‐month‐old malformed foetus revealed hydrocephalus, torticollis and arthrogryposis. Foetal brain tissue and blood were found to be SBV‐positive by RT‐PCR and ELISA tests, respectively. Evidencing the circulation of SBV in Belgium in the autumn 2015 is important to anticipate future outbreaks and advise veterinarians about the risks associated with calving, as more bovine foetuses might have been infected.